2020
DOI: 10.6004/jnccn.2020.7601
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating if an Advance Care Planning Intervention Promotes Do-Not-Resuscitate Orders by Facilitating Accurate Prognostic Awareness

Abstract: Background: Issuing do-not-resuscitate (DNR) orders has seldom been an outcome in randomized clinical trials of advance care planning (ACP) interventions. The aim of this study was to examine whether an ACP intervention facilitating accurate prognostic awareness (PA) for patients with advanced cancer was associated with earlier use of DNR orders. Patients and Methods: Participants (n=460) were randomly assigned 1:1 to the experimental and control arms, with 392 deceased participants constituting the final samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…[7][8][9] In developed countries, the advantages of ACP have been well documented with comprehensive, in-depth research on a wide range of research populations, including adolescents, adults, the elderly, and their families. 10,11 In China, the population focused on in research are patients with advanced cancer or in the terminal stage 12,13 ; family members are rarely included. The research content is also mainly focused on knowledge of and attitude toward ACP, 14 and there are few behavior studies on ACP participation.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In developed countries, the advantages of ACP have been well documented with comprehensive, in-depth research on a wide range of research populations, including adolescents, adults, the elderly, and their families. 10,11 In China, the population focused on in research are patients with advanced cancer or in the terminal stage 12,13 ; family members are rarely included. The research content is also mainly focused on knowledge of and attitude toward ACP, 14 and there are few behavior studies on ACP participation.…”
Section: Introductionmentioning
confidence: 99%
“…The recent systematic reviews on the efficacy of ACP based on 132 RCTs concluded that it improved ACP documentation, with 34 out of 54 included studies (63%) showing significant and positive results [12]. However, amongst these 54 RCTs, only three were conducted in Asian countries [28,30,31]. Together with a more recent RCT in Singapore, mixed results on ACP/AD documentation were found: two showed significant improvement in the outcome [28,30], and the other two had non-significant results [31,32].…”
Section: Results Of Logistic Regression On Primary Outcome and Genera...mentioning
confidence: 99%
“…However, amongst these 54 RCTs, only three were conducted in Asian countries [28,30,31]. Together with a more recent RCT in Singapore, mixed results on ACP/AD documentation were found: two showed significant improvement in the outcome [28,30], and the other two had non-significant results [31,32]. Compared with our previous RCT on ACP conducted in Hong Kong with significant results on ACP/AD documentation [28], we did not observe a difference in the AD completion rate between the two groups although we have added the 3-min video decision aid in the ACP intervention in the current study.…”
Section: Results Of Logistic Regression On Primary Outcome and Genera...mentioning
confidence: 99%
“…DNR orders: None of the five RCTs that explored the effect of ACP on do-not-resuscitate (DNR) orders found a significant association 52 69 131 150 151…”
Section: Resultsmentioning
confidence: 99%